(untitled) (Educational Dimension, 2020)
The article presents the research findings received throughout the study in the general secondary educational institutions in Ukraine. The processes of creation, receipt, processing and submission of information to the end consumer are substantiated and practically verified, namely, the system of information quality assurance of education quality management in the general educational institution is methodologically substantiated. Questionnaires were developed and conducted for GEI executives and administrative and management staff who are the part of the methodology for studying the state of the informational support for the quality management of education at GEI. It is established that not only the knowledge of the external information content, which is necessary for the implementation of the cycle of the educational quality management in the educational institution, but also the sources of its receipt and creation is of great importance for the heads of the general educational institutions.